Learning from postneoliberalisms. (October 2017) - Elwood, Sarah; Bond, Patrick; Novo, Carmen Martínez; Radcliffe, Sarah
This forum examines a range of grounded struggles over efforts to materialize elements of a 'postneoliberal' agenda by social and political movements of the 2000s. Drawing from their research in Latin America and South Africa, the contributors ask when, where and why these experiments in realizing postneoliberalisms have prompted durable transformations in neoliberal political economic structures and social rationalities (or not). Theorizing from diverse postneoliberalisms, they interrogate what these material and ideological projects reveal about space, power, contestation, and possibilities of reconstituting deeply unequal worlds.